Transparency in Local Government Health and Education service Delivery in Dodoma, Tanzania - Likangaga, Rose; Kumburu, Neema; Panga, Faustine (Journal of Policy and Leadership, 2022)
Effective Local Government education and health service delivery requires a sound transparency system in place. However, the literature suggests that the absence of effective transparency particularly in local government determines the quality-of-service delivery. Therefore, this paper aims at exploring the functionality of transparency in LGA service delivery; More specifically the paper aims to identify the openness and honesty of local government officials, examine the citizen information accessibility and assess the influence of open decision-making in LGAs services delivery. The crosssectional research design was employed. The study involved 399 respondents from villages and streets (Mtaa) including 15 key informants. Secondary data were obtained from the villages and streets (Mtaa) meetings log books, council financial reports as well as previous assembly meeting minutes. Quantitative data were analysed through factor analysis and stereotype logistic regression mode while qualitative data were analysed through content analysis. Unfortunately, the contribution of transparency to LGAs services delivery is minimal. The results revealed that there was a negative association between transparency and education and health service delivery. However, this cannot deny the ordinal information, which revealed that a minor relationship exists between the variables. The major concern for low transparency in LGAs might be the inadequate chain of command in the Tanzania LGAs framework. Additionally, most local government authorities in Tanzania use low-level technology. Thus, it is recommended that the Regulatory framework should be adjusted to ensure LGAs officials are more transparent. Further, these should go together with ICT innovation in LGAs setting towards effective transparency in LGAs for improved education and health service delivery.